Reliability and construct validity of the Activities Scale for Kids in Italian children with cerebral palsy. Issue 21 (9th October 2022) - Costi, Stefania; Filippi, Maria Cristina; Braglia, Luca; Beccani, Laura; Corradi, Isabella; Bruzzi, Elena; Signorelli, Chiara; Pelosin, Elisa
Abstract: Purpose: To investigate internal consistency and construct validity of the of the Activities Scale for Kids performance (ASKp) in Italian children with cerebral palsy (CP). Methods: This cross-sectional study was conducted from 2014 up to 2019 and consisted in the single self-administration of the Italian ASKp to 206 children aged 5–15, with unilateral or bilateral CP, classified on the basis of the Gross Motor Function Classification System (GMFCS). Results: The ASKp showed good internal consistency (Chronbach's α 0.91, 95% CI 0.89–0.93). It distinguished between children and adolescents (70.3 ± 16.6 versus 83.0 ± 18.0, respectively; p  < 0.001), unilateral and bilateral CP clinical manifestations (82.5 ± 13.6 versus 72.4 ± 19.0, respectively; p  = 0.002), children with and without intellectual disability (60.3 ± 18.3 versus 77.2 ± 17.3, respectively; p  < 0.001). It also distinguished children using assistive devices for indoor mobility from children who did not use devices or those who use devices only for outdoor mobility (66.1 ± 18.3 versus 83.6 ± 12.8 and versus 80.4 ± 17.4, respectively; both p  < 0.001). Conclusions: The ASKp could help integrate the perspective of children with CP in their rehabilitation process. Trial registration: ClinicalTrials.gov Identifier: NCT03325842 IMPLICATIONS FOR REHABILITATION: The ASKp is a valid and widely used measure for several ICF domains of activities and participation in pediatrics. It has never been formally validated in children with CP, although this disorder causes restrictions in everyday activities. Recently, the culturally adapted Italian version of the ASKp has been tested in typically developing Italian children, confirming its high acceptability and providing evidence of construct validity. This study confirms the internal consistency reliability and the construct validity of the Italian ASKp when applied to the population with CP. The ASKp can support rehabilitation professionals in planning therapeutic intervention targeted to relevant goals.